2023
DOI: 10.3389/fonc.2023.1099943
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinases in nodal peripheral T-cell lymphomas

Abstract: Nodal peripheral T-cell lymphomas (PTCL) are uncommon and heterogeneous tumors characterized by a dismal prognosis. Targeted therapy has been proposed. However, reliable targets are mostly represented by a few surface antigens (e.g., CD52 and CD30), chemokine receptors (e.g., CCR4), and epigenetic gene expression regulation. In the last two decades, however, several studies have supported the idea that tyrosine kinase (TK) deregulation might be relevant for both the pathogenesis and treatment of PTCL. Indeed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Among the highlights, it is noteworthy that combination treatments provide successful results. It is suggested that checkpoint inhibitors and epigenetic modifiers combined with TKI may show significant effectiveness in many types of cancer, including lymphoma cells [31,32]. For the targeted treatment of unresectable HCC, Lenvatinib, Cabozantinib, Ramucirumab and Regorafenib have been approved [33].…”
Section: Discussionmentioning
confidence: 99%
“…Among the highlights, it is noteworthy that combination treatments provide successful results. It is suggested that checkpoint inhibitors and epigenetic modifiers combined with TKI may show significant effectiveness in many types of cancer, including lymphoma cells [31,32]. For the targeted treatment of unresectable HCC, Lenvatinib, Cabozantinib, Ramucirumab and Regorafenib have been approved [33].…”
Section: Discussionmentioning
confidence: 99%
“…While the establishment of an overt lymphoid malignancy is almost universally a stepwise process, lymphomas expressing anaplastic lymphoma kinase (ALK) and, seemingly, similarly powerful oncogenic kinases ( 35 37 ) are a notable exception ( Figure 2 ). ALK, typically expressed as the NPM1-ALK (NPM1::ALK) hybrid protein due to t(2;5) chromosomal translocation resulting in fusion of the involved genes, profoundly reprograms targeted CD4+ T cells by conferring upon these cells features required for a full-fledged malignant cell transformation ( 38 , 39 ).…”
Section: Malignant Transformation Of T and B Lymphocytes Driven By Ch...mentioning
confidence: 99%
“…These chromosome 6p25.3 rearrangements confer an overall better prognosis, according to some studies ( 48 , 49 ). In other ALK-negative ALCL cases, translocations and related persistent expression of genes encoding tyrosine kinases, to some degree functionally analogous to ALK, has been identified ( 36 , 37 , 48 ). While one of these ALK-like kinases ROS1, is structurally closely related to ALK, the other two:TYK2 and JAK2 are members of the JAK tyrosine kinase family.…”
Section: Malignant Transformation Of T Lymphocytes Driven By Other Po...mentioning
confidence: 99%
See 2 more Smart Citations